EFFECT OF SHORT AND LONG TERM DEBT TO PROFITABILITY IN THE MINING INDUSTRY LISTED IN JSX - Hendri Dwilaksono (Universitas Trisakti, 2010)
The objective of this research is to find the influence of Short Term Debt and Long Term Debt on Return On Equity in mining industry listed in Indonesia Stock Exchange. This research used qualitative and quantitative methods, meanwhile this analysis of data processing used regression analysis by SPSS program. Mining industry Companies listed in Indonesia Stock Exchange in2003-2007 had chosen as the population of this research. Data analysis applied measuring method by regression analysis model then be estimated by ordinary least square. The analysis result as individual shows Short Term Debt variable have a positive influence and significant on Return On Equity, Long Term Debt variable have a negative influence and significant on ReturnOn Equity. The analysis result as simultaneous shows there is influence of Short Term Debt and Long Term Debt to Return On Equity. Long Term Debt variable is a dominant variable influences to Return On Equity